2012
DOI: 10.1136/tobaccocontrol-2012-050739
|View full text |Cite
|
Sign up to set email alerts
|

Examining market trends in the United States smokeless tobacco use: 2005–2011

Abstract: Background While cigarette consumption in the USA continues to decline, promotion for and consumption of smokeless tobacco (SLT) is growing. However, little research has explored what product features are driving SLT growth, despite awareness that product-level factors may be important in SLT use. This study analyses national sales data to better understand the impact of product features on SLT sales. Methods Data on sales of SLT in US convenience stores from 2005 to 2011 were obtained from Nielsen Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
133
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 14 publications
3
133
0
Order By: Relevance
“…Males were more likely to have heard of snus and were about three times more likely to report snus use compared with females. This may indicate that disproportionate marketing of smokeless tobacco to males contributes to snus awareness and use (Delnevo et al, 2014). Non-Hispanic White participants were the most likely to be aware of snus compared with other racial/ ethnic groups, but race/ethnicity was not significantly associated with snus use.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Males were more likely to have heard of snus and were about three times more likely to report snus use compared with females. This may indicate that disproportionate marketing of smokeless tobacco to males contributes to snus awareness and use (Delnevo et al, 2014). Non-Hispanic White participants were the most likely to be aware of snus compared with other racial/ ethnic groups, but race/ethnicity was not significantly associated with snus use.…”
Section: Discussionmentioning
confidence: 91%
“…Despite well-documented health risks, the prevalence of current smokeless tobacco use among U.S. adults aged 18 years and older is 3.4%, and 1.4% of adults use snus (King, Dube, & Tynan, 2012). Sales of pouched forms of moist snuff increased by 333.8% between 2005 and 2011, with snus sales doubling between 2009 and 2010 and snus brands emerging among the top 10 selling moist snuff brands after just 2 years on the U.S. market (Delnevo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 Sales of moist snuff products increased by 65.6 % between 2005 and 2011. 2 In addition, consuming two or more tobacco products-referred to as polytobacco use and also known as multiple tobacco product use, concurrent tobacco use, and concomitant tobacco use-has become increasingly common. [3][4][5] According to the 2012 National Survey on Drug Use and Health data, 10.1% of young adults aged 18−25 and 3.7% of adults aged ≥26 were current polytobacco users.…”
Section: Introductionmentioning
confidence: 99%
“…Research using Minnesota statewide data found the proportion of cigarettes smokers reporting ST use increased between 2007 and 2010 [18]. It has been suggested that the increase in ST use among smokers may be due to wide implementation of in-home and public smoking bans nationwide and the tobacco industry marketing of ST as a substitute for cigarettes when smoking is not permitted [48]. However, many of our study data pre-date these more recent trends in policy and marketing, with many Y-K smokers reporting concurrent use well before public bans.…”
Section: Discussionmentioning
confidence: 99%